2014
DOI: 10.1186/1471-2393-14-331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lifestyle intervention on dietary intake, physical activity level, and gestational weight gain in pregnant women with different pre-pregnancy Body Mass Index in a randomized control trial

Abstract: BackgroundThe objectives of this study were to assess the efficacy of lifestyle intervention on gestational weight gain in pregnant women with normal and above normal body mass index (BMI) in a randomized controlled trial.MethodsA total of 116 pregnant women (<20 weeks of pregnancy) without diabetes were enrolled and 113 pregnant women completed the program. Participants were randomized into intervention and control groups. Women in the intervention group received weekly trainer-led group exercise sessions, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
142
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(158 citation statements)
references
References 14 publications
4
142
1
11
Order By: Relevance
“…Mottola (2009) has suggested that interventions for pregnant women need to be behaviour-based because education programs increase knowledge, but do not change behaviour. This is consistent with Hui (Hui et al, 2014), showing that participating in a lifestyle intervention can increase physical activity level.…”
Section: Introductionsupporting
confidence: 78%
“…Mottola (2009) has suggested that interventions for pregnant women need to be behaviour-based because education programs increase knowledge, but do not change behaviour. This is consistent with Hui (Hui et al, 2014), showing that participating in a lifestyle intervention can increase physical activity level.…”
Section: Introductionsupporting
confidence: 78%
“…Our finding was surprising because other previous significant results (4-6) are related to normal women. Hui et al's trial performed on different pre-pregnancy BMI could decrease excessive GWG in normal, but not in above-normal pregnant women (8).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies could show gestational weight gain reduction in normalweight (8) and obese women (23,24) or could not show any change at all (8,(25)(26)(27). Only Asbee et al indicated a reduction in gestational weight in women with different BMIs including normal, overweight, and obese categories (28).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations